ANALISIS PEMETAAN POTENSI SITUS BEKAS KERATON MATARAM KARTASURA UNTUK PENGEMBANGAN WISATA HERITAGE DI KABUPATEN SUKOHARJO - Henny Kustini; Anita Andriantini Mulia (Journal of Tourism Destination and Attraction, 2020)
The purpose of this research is to identify problems and develop tourism potential in the site of the former Mataram Kartasura palace based on the emerging potential. This type of research is qualitative research with descriptive analysis. Data obtained from interviews with a number of 6 sources, both from the management of the former Mataram Kartasura palace, the Sukoharjo district government and also the Surakarta Kasunanan. The interview data were processed and analyzed using the SWOT analysis technique. Identification of problems that arise in the object of the former Mataram Kartasura palace, namely around the object of revitalization which is considered difficult, the role of the community is less active, the potential of the surrounding area that can boost the object of the former palace, management that has not been synergized, labor problems, transportation accommodation is not optimal, policy weaknesses local government of Sukoharjo. Therefore, this research is divided into 3 things, namely products, marketing and institutions by increasing the strengths and opportunities of the objects of the former Mataram Kartasura palace and minimizing the weaknesses and threats of emerging potentials.